If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -1x = x + -24 Reorder the terms: 4 + -1x = -24 + x Solving 4 + -1x = -24 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 4 + -1x + -1x = -24 + x + -1x Combine like terms: -1x + -1x = -2x 4 + -2x = -24 + x + -1x Combine like terms: x + -1x = 0 4 + -2x = -24 + 0 4 + -2x = -24 Add '-4' to each side of the equation. 4 + -4 + -2x = -24 + -4 Combine like terms: 4 + -4 = 0 0 + -2x = -24 + -4 -2x = -24 + -4 Combine like terms: -24 + -4 = -28 -2x = -28 Divide each side by '-2'. x = 14 Simplifying x = 14
| 14y+5=2 | | 3x+2(.5x-x)=4 | | 13/4z=39 | | x/4log10(4x) | | 0.01=x/12 | | 10-2(x-4)=x+23 | | 10y-7-7y= | | 5x-3(7x+5)=1 | | 3.75z=39 | | 34/100= | | x/-5-(-9)=0 | | -20n-71=n+706 | | 4=-4x+8 | | y/-5-(-9)=0 | | 7.27-6.36= | | d+130=-4d-30 | | 15=7.5y-8 | | d-443=-30d-9 | | 80.00/15 | | 6n+47=n-68 | | x-5*x=42 | | 8+p=6 | | 16x+6=x-714 | | 2/3y-1/3=2 | | b-116=-3b-8 | | y-107=6y-7 | | -2d-8=d-83 | | 17.5=2.5(7.5y-8) | | 3.50s+t=44 | | 6c+4=c-81 | | 5(m-3)+(m-4)= | | 2c+2d+6d= |